Molecular cloning of a human melanoma-associated chondroitin sulfate proteoglycan. - Pluschke, G (1996)
A human melanoma-associated chondroitin sulfate proteoglycan (MCSP), recognized by mAb 9.2.27, plays a role in stabilizing cell-substratum interactions during early events of melanoma cell spreading on endothelial basement membranes. We report here the molecular cloning and nucleotide sequencing of cDNA encoding the entire core protein of human MCSP and provide its deduced amino acid sequence. This core protein contains an open reading frame of 2322 aa, encompassing a large extracellular domain, a hydrophobic transmembrane region, and a relatively short cytoplasmic tail. Northern blot analysis indicated that MCSP cDNA probes detect a single 8.0-kb RNA species expressed in human melanoma cell lines. In situ hybridization experiments with a segment of the MCSP coding sequence localized MCSP mRNA in biopsies prepared from melanoma skin metastases. Multiple human Northern blots with an MCSP-specific probe revealed a strong hybridization signal only with melanoma cells and not with other human cancer cells or a variety of human fetal and adult tissues. These data indicate that MCSP represents an integral membrane chondroitin sulfate proteoglycan expressed by human malignant melanoma cells. The availability of cDNAs encoding MCSP should facilitate studies designed to establish correlations between structure and function of this molecule and help to establish its role in the progression of human malignant melanoma.